BRAIN WRITING LEARNING MODEL USING EPISODIC MEMORY IN TEACHING NARRATIVE TEXT - Andi Hamzah Fansury; Restu Januarty; Asdar Asdar (Universitas Muhammadiyah Makassar, 2018)
The aims of this study was (1) To find out the significant brain writing learning model using episodic memory in teaching narrative texts (2) to determine the students' interest in applying brain writing learning model using episodic memory in teaching narrative text. This study used quasi-experimental method. This research was conducted at SMPN 30Makassar with total number population consist of 810 students. The researcher used a random sampling technique. The total sample used was 60 students. The researcher divided the sample into two classes, namely the experimental class and the control class. The instruments of the research were tests, questionnaires and interviews. Based on data analysis, it can be concluded that brain writing learning model using episodic memory in teaching narrative texts not significantly improve the students achievement especially in writing narrative text. Brain writing learning model using episodic memory also is very effective to be applied to avoid student boredom and make students more interest in learning process.